Facile preparation of nanostructured alpha-Fe2O3 thin films with enhanced photoelectrochemical water splitting activity - Rahman, Gul; Joo, Oh-Shim (ROYAL SOC CHEMISTRY, 2013)
We report on the use of a facile electrospray technique for the synthesis of alpha-Fe2O3 thin films on a FTO substrate for photoelectrochemical (PEC) water splitting. The effect of synthesis parameters such as substrate temperature, discharge potential and post-heat treatment on morphology, particle size and PEC performance of alpha-Fe2O3 films were investigated. With an increase in substrate temperature, the surface morphology of the alpha-Fe2O3 film was altered from a packed worm-like surface to highly porous nanostructures. XRD analysis revealed that the (110) grain orientation of the film was transformed to the (104) grain orientation at 300 degrees C, due to the oxidation of the precursor at the surface of the substrate. Raman spectroscopy and XPS analysis indicated the presence of highly pure alpha-Fe2O3 in the film. By changing the discharge potential, the size of particles in the film was reduced to a minimum of 23 nm. Under optimized conditions the nanostructured alpha-Fe2O3 films showed a water splitting photocurrent of similar to 0.6 mA cm(-2) at 1.23 V versus RHE under standard illumination conditions (AM 1.5 G 100 mW cm(-2)), and an incident photon to current efficiency (IPCE) of 13% at 350 nm (at 1.4 V versus RHE) which are among the best results obtained for undoped alpha-Fe2O3 photoanodes. This enhanced PEC performance can be attributed to the efficient charge separation at the alpha-Fe2O3-electrolyte interface due to the larger interfacial area of small-sized particles in the film. This study thus provides a simple route for the synthesis of highly active alpha-Fe2O3 thin films that can be extended to metal doped films such as Ti-doped alpha-Fe2O3.
Keywords: IRON-OXIDE FILMS; HYDROGEN-PRODUCTION; HEMATITE PHOTOANODES; CARRIER DYNAMICS; OXIDATION; PERFORMANCE; GENERATION; DEPOSITION; TI; ELECTRODES